Asymptomatic pulmonary penicilliosis with a lung mass in an HIV‐infected patient. (13th May 2020) - Nishikubo, Masashi; Doi, Asako; Takegawa, Hiroshi; Yamashita, Daisuke; Ohira, Junichiro; Nishioka, Hiroaki
Abstract: Penicillium marneffei ( Talaromyces marneffei ) infection sometimes occurs in HIV‐infected patients in South‐East Asia. However, reports on asymptomatic cases are rare. Herein, we report a case of a 27‐year‐old Burmese HIV‐positive woman with pulmonary penicilliosis. Chest radiography showed a lung mass; however, the patient did not have any respiratory symptoms. Cultures of bronchoalveolar lavage and lung tissue grew P marneffei . The patient was diagnosed with penicilliosis and successfully treated with amphotericin B and itraconazole. Our findings suggest that P marneffei infection should be considered in the differential diagnosis of a lung mass in HIV‐infected patients, even when asymptomatic for respiratory symptoms. Abstract : We report the case of pulmonary penicilliosis, which showed a lung mass on chest radiography but without respiratory symptoms. Reports on asymptomatic cases are rare.